The water-soluble fraction of extracellular polymeric substances from a resource recovery demonstration plant: characterization and potential application as an adhesive - Chen, Le Min; Erol, Özlem; Choi, Young Hae; Pronk, Mario; van Loosdrecht, Mark; Lin, Yuemei (Frontiers in Microbiology, 2024)
There is a growing interest currently in transforming wastewater treatment plants into resource recovery plants. Microorganisms in aerobic granular sludge produce extracellular polymeric substances (EPS) which is considered a sustainable resource to be extracted and can be used in diverse applications. Exploring applications in other high-value materials, such as an adhesive, will not only enhance the valorization potential of the EPS, but also promote resource recovery. This study aims to characterize a water-soluble fraction extracted from the EPS collected at the demonstration plant in the Netherlands on the chemical composition (amino acids, sugar and fatty acids) and propose a proof-of-concept for its use as an adhesive. This fraction comprises of a mixture of biomolecules, such as proteins (26.6 ± 0.3%), sugars (21.8 ± 0.2%) and fatty acids (0.9%). The water-soluble fraction exhibited shear strength reaching 36 – 51 kPa across a pH range of 2 – 10 without additional chemical treatment, suggesting a potential application as an adhesive. The findings from this work provides insights into the concept of resource recovery and valorization of the excess sludge at wastewater treatment plant.